The effectiveness of open-ended worksheet-based learning in exponential material to enhance middle school students’ mathematical conceptual understanding - Amelia, Rosa; Nurlaela, Nurlaela (Papanda Publisher, 2024)
This study investigates the effectiveness of open-ended LKPD (Lembar Kerja Peserta Didik) on the topic of exponents in enhancing the mathematical conceptual understanding of middle school students. The research employed a pre-experimental design using the One-Group Pretest-Posttest Design. This design was chosen because the study involved a single experimental group, and the comparison was made between students’ pre-test and post-test scores. Data analysis using the t-test revealed a t-count of 7.741. At a significance level of 5%, the t table value was 1.711, indicating that t count ≥ t table (7.741 ≥ 1.711). Based on hypothesis testing, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. These results suggest that the use of open-ended LKPD significantly improves students’ ability to solve mathematical problems related to exponents. The findings imply that incorporating open-ended worksheets in mathematics instruction can effectively enhance students’ conceptual understanding and problem-solving skills.